2023
DOI: 10.1021/acs.jpclett.2c03928
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Raman Study of Voltage Tolerance Up to 2.2 V of Ionic Liquid Analogue Supercapacitor Electrolytes Immune to Water Adsorption Conferred by Amphoteric Imidazole Additives

Abstract: Ionic liquid analogues (ILAs) are promising electrolytes for supercapacitors due to their low cost and considerable voltage (>2.0 V). However, the voltage is <1.1 V for water-adsorbed ILAs. Herein for the first time, an amphoteric imidazole (IMZ) additive is reported to address this concern by reconfiguring the solvent shell of ILAs. Addition of only 2 wt % IMZ increases the voltage from 1.1 to 2.2 V, with an increase in capacitance from 178 to 211 F g–1 and an increase in energy density from 6.8 to 32.6 Wh kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Raman spectra revealed that the components’ characteristic peaks of C–N (at ∼724 cm –1 ) and C–H (at 2800–3100 cm –1 ) in ChCl and C–O (at 800–960 cm –1 and ∼1050 cm –1 ) and O–H (at 3100–3600 cm –1 ) in TEOA coexist in ILA 1:2 , ILA 1:5 , ILA 1:10 , and ILA 1:20 (Figure b), demonstrating the formation of ILAs due to the weak interactions between H-bond donors and H-bond acceptors, such as O–H···O, O–H···Cl, and O–H···N, as well as the additional Coulombic action between ions . The corresponding Raman spectra focusing on the part of H-bonding interactions are magnified in Figure c; in contrast to the predominantly strong H-bonding interactions in ChCl, the H-bonding interactions in TEOA can be divided into the three components of strong (at ∼3255 cm –1 ), weak (at ∼3382 cm –1 ), and non-H-bonds (at ∼3478 cm –1 ) . The H-bonding interactions of ILA 1:2 , ILA 1:5 , ILA 1:10 , and ILA 1:20 mainly consist of strong and weak H-bond components.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Raman spectra revealed that the components’ characteristic peaks of C–N (at ∼724 cm –1 ) and C–H (at 2800–3100 cm –1 ) in ChCl and C–O (at 800–960 cm –1 and ∼1050 cm –1 ) and O–H (at 3100–3600 cm –1 ) in TEOA coexist in ILA 1:2 , ILA 1:5 , ILA 1:10 , and ILA 1:20 (Figure b), demonstrating the formation of ILAs due to the weak interactions between H-bond donors and H-bond acceptors, such as O–H···O, O–H···Cl, and O–H···N, as well as the additional Coulombic action between ions . The corresponding Raman spectra focusing on the part of H-bonding interactions are magnified in Figure c; in contrast to the predominantly strong H-bonding interactions in ChCl, the H-bonding interactions in TEOA can be divided into the three components of strong (at ∼3255 cm –1 ), weak (at ∼3382 cm –1 ), and non-H-bonds (at ∼3478 cm –1 ) . The H-bonding interactions of ILA 1:2 , ILA 1:5 , ILA 1:10 , and ILA 1:20 mainly consist of strong and weak H-bond components.…”
Section: Resultsmentioning
confidence: 99%
“…Their morphologies and element contents were analyzed by scanning electron microscopy (SEM, FEI Scios 2 HiVac, 31 The corresponding Raman spectra focusing on the part of H-bonding interactions are magnified in Figure 1c; in contrast to the predominantly strong H-bonding interactions in ChCl, the H-bonding interactions in TEOA can be divided into the three components of strong (at ∼3255 cm −1 ), weak (at ∼3382 cm −1 ), and non-H-bonds (at ∼3478 cm −1 ). 27 The H-bonding interactions of ILA 1:2 , ILA 1:5 , ILA 1:10 , and ILA 1:20 mainly consist of strong and weak H-bond components. With the increase of TEOA content, the ratio of strong H-bonds to total H-bonds (A s /A t ) in ILAs decreases from 0.68 to 0.42, and the FTIR spectra of the ILAs also show the existence of H-bond peaks at 3100−3600 cm −1 in the ILAs (Figure S1).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] Traditional attempts to boost E often begin by increasing the specific capacitance (C) of porous carbon (e.g., by increasing specific surface area, SSA) or the voltage window of electrolytes (e.g., by introducing novel electrolyte components). [9][10][11][12][13][14] Theoretically, C is proportional to SSA, but if SSA exceeds a certain threshold (e.g., 1200 m 2 g −1 ), the rise in C slows down and approaches its limit (i.e., even a considerable increase in SSA does not increase C proportionally). [15] It implies that in electrode-electrolyte systems, C should be connected to parameters other than SSA.…”
Section: Introductionmentioning
confidence: 99%